Plataforma para orquestração de serviços para cuidados continuados de saúde - Silva, Eliseu Germano da (2019)
A care plan is a set of information that links patients to their therapy. This work proposes modeling ubiquitous care plans as a set of patient-centered computing resources. These resources are modeled as services that are orchestrated by workflows. In order to allow a health professional to be able to build these workflows using services that handle the specificities of a patient's treatment, we propose a platform that receives the description of the workflows, created using a DSL script, orchestrates the services specified in the script and makes workflows available as a new service. Partly as a result of this research, we implemented some of the components of this platform, such as a DSL, a computer model to represent the workflow at runtime, and the required mechanisms for communication with the services. This platform has been tested with the use of healthcare scenarios where practical management situations for care plan tasks have been automated by means of the implementation and registration of web services. Using the DSL, some workflows were built to test the services registered on the platform and to evaluate some issues related to service composition, workflow reuse and computational resource consumption.